Peningkatan Kompetensi Guru dalam Mengembangan Modul Ajar dengan Pendekatan CRT dan Berbantuan Artificial Intelegence - Deddiliawan Ismail, Agung; inganah, siti; Nadlifah, Minatun; Ekowati, Dyah Worowirastri (Bakti Cendana, 2025)
Teachers play a role in their professional development, continuously improving their skills and knowledge through training and ongoing education. They must stay updated on the latest teaching methods and expertise to ensure they provide relevant and up-to-date education. Based on interviews with the school principal and the curriculum vice principal, a problem was identified: teachers were not optimizing their lesson module design due to the numerous tasks they had to complete. Therefore, support is needed to help teachers create lesson modules more efficiently. he proposed solution is to provide guidance in developing lesson modules using the Culturally Relevant Teaching (CRT) approach with AI assistance. Data analysis before and after the mentoring process showed significant improvement among participants. For the CRT concept comprehension indicator, local cultural integration, and culturally responsive lesson module development, there was an improvement from the "needs improvement" to "good" category. Regarding AI comprehension, there was an improvement from "fair" to "good." In the use of AI for lesson module development, the improvement was even more substantial, from "needs improvement" to "very good".